2021
DOI: 10.3390/ani11041096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mesh and Barbed Suture for Laparoscopic Nephrosplenic Space Ablation in Horses

Abstract: Nephrosplenic space (NSS) ablation has been demonstrated to be an effective technique for prevention of left dorsal displacement of the large colon and multiple laparoscopic techniques, among which ablation with mesh or with a barbed suture, have been proposed. Our objective was to compare two laparoscopic techniques for closure of the NSS in twenty-eight horses diagnosed with nephrosplenic entrapment. Medical records of horses that had laparoscopic NSS ablation in two referral centers between 2017–2019 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Reports about the use of barbed sutures in equine laparoscopic procedures in clinical cases are not abundant but promising. For example, laparoscopic nephrosplenic space ablation using barbed suture has been successfully employed (Gandini et al, 2017; Gialletti et al, 2021) and was evaluated advantageous over mesh ablation (Gialletti et al, 2021). Corsalini and colleagues used unidirectional barbed suture for laparoscopic uteropexy in three mares (Corsalini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports about the use of barbed sutures in equine laparoscopic procedures in clinical cases are not abundant but promising. For example, laparoscopic nephrosplenic space ablation using barbed suture has been successfully employed (Gandini et al, 2017; Gialletti et al, 2021) and was evaluated advantageous over mesh ablation (Gialletti et al, 2021). Corsalini and colleagues used unidirectional barbed suture for laparoscopic uteropexy in three mares (Corsalini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In equine surgery, the use of barbed sutures has been investigated ex vivo as well as in clinical cases for different open and laparoscopic applications (Adler et al, 2020;Albanese et al, 2016;Corsalini et al, 2016;Gandini et al, 2017;Gialletti et al, 2021;Giusto, Caramello, et al, 2019;Kamus et al, 2022;Major et al, 2017;Nelson & Hassel, 2014;Ruzickova et al, 2016;Sinovich et al, 2020). Ragle and colleagues first described laparoscopic vaginal ring closure with an automated suturing instrument and barbed suture in an adult gelding with an acquired inguinal hernia (Ragle et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different techniques and materials are described to close the space: these include simple suture material, barbed sutures and various implants. 14,16,17 A standard left laparoscopic approach allows for visualization of the nephrosplenic space. A large diameter (25-30 mm) cannula is introduced through the most dorsal left flank portal to allow for direct vision of the nephrosplenic space and to facilitate suturing.…”
Section: Nephrosplenic Entrapment Of the Ascending Colon And Closure ...mentioning
confidence: 99%
“…It is first attached to the renal fascia and then to the splenic capsule using laparoscopic staples or tacking devices. 16,19 Gialletti and colleagues compared the use of mesh and barbed suture for nephrosplenic space ablation and concluded that the suture was faster, more cost-efficient and caused fewer complications. 16 Spagnolo and colleagues described the use of homologous pericardium implants harvested from horses euthanized for orthopedic disease.…”
Section: Nephrosplenic Entrapment Of the Ascending Colon And Closure ...mentioning
confidence: 99%